Valuing the effects of mining critical minerals : The Per Geijer deposit in Kiruna - Krigsman, Olivia (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2024)
Critical raw materials have become an important part in the green transition, and EU is not self-sufficient to secure the supply EU needs. LKAB recently released that the Per Geijer deposit in Kiruna contains large amounts of some critical raw materials, for example rare earth metals. If a mining permit of the deposit is approved, an additional mine would operate in Kiruna. There are different effects from mining, and some can be difficult to evaluate, since the effects may not hold a market price. Therefore, this study intends to assess effects caused by mining of the Per Geijer deposit in Kiruna. A choice experiment is applied which includes the effects of mining on the attributes; reindeer husbandry, outdoor activities and new job opportunities, together with a cost attribute of a potential municipal tax increase. The result identified a significant negative economic impact on both reindeer husbandry and outdoor activities, but positive on potential job opportunities. As well, men and those working in mine related areas are more willing to choose the ‘approved permit for mining’ option.